Paraprotein-related renal disease. (April 2023) - Pinney, Jennifer H.; Rana, Ritika; Lachmann, Helen J.
Abstract: Paraprotein-related renal disease encompasses a group of rare diseases characterized by distinct renal injury caused by the direct or indirect effects of a nephrotoxic paraprotein. Individuals can present with proteinuric renal impairment or, more rarely, tubular dysfunction. Diagnosis is often challenging because of the wide range of disease manifestations, difficulties with detection of the pathogenic clone and the common finding of an incidental paraprotein in elderly individuals. The combination of a renal biopsy along with a full haematological work-up is required to link a paraprotein to kidney disease. Chemotherapy directed at the plasma cell clone can halt the production of the paraprotein, which can in turn benefit renal function. Early diagnosis and the use of rapidly effective chemotherapy agents have improved patient and renal outcomes for these disorders.